High‐Temperature Oxidation‐Resistant Printed Copper Conductors. (21st December 2022) - Khuje, Saurabh; Alshatnawi, Firas; Alhendi, Mohammed; Yu, Jian; Sheng, Aaron; Huang, Yulong; Zhuang, Cheng‐Gang; Armstrong, Jason; Zhou, Chi; Poliks, Mark; Ren, Shenqiang
Abstract: Advanced materials, electrically conductive and oxidation resistant, are frontrunners for technological advancements in cutting‐edge high‐temperature electronics. Rational design and manufacturing of hierarchical material structures is indispensable to achieve such disparate functionalities. Here, high‐temperature copper–graphene conductors, through additive manufacturing, which prohibits oxygen adsorbates and serves as the barrier for oxygen migration to enable electric stability and reliability at high temperatures, are reported. The combination of graphene and alumina surface passivation enables the electric stability of copper–graphene under thermal impact above 1000 °C. The findings shown here, the synergistic combination of high conductivity and oxidation resistance, enunciate the passivation capabilities for additively manufactured flexible electronics operating under harsh conditions. Abstract : High‐temperature copper–graphene conductors, through additive manufacturing for flexible electronics operating under harsh conditions, are reported. The synergistic combination of graphene and ceramic passivation enables oxidation resistance and electric stability of copper–graphene under high temperatures.